2016
DOI: 10.1007/s13555-016-0163-0
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Side Effects and Transepidermal Water Loss To Gefitinib: A Study of 11 Patients

Abstract: IntroductionCutaneous side effects caused by epidermal growth factor receptor (EGFR) inhibitors occurred in 45–100% of patients which may lead to therapy modification or interruption. This study aimed to evaluate cutaneous side effects and transepidermal water loss (TEWL) values in non-small cell lung carcinoma (NSCLC) patients who received gefitinib EGFR inhibitor.MethodsA descriptive observational study with cross-sectional design and a consecutive sampling method was conducted from 1 February to 4 March 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The risk of skin dryness during treatment increases with age, pre-eczema, and prior cytotoxic use. Evidence showed patients who received gefitinib experienced xerosis cutis, acneiform have mean Transepidermal Water Loss values higher than normal (46). The different degrees of severity of the xerosis are illustrated in Figure 2.…”
Section: Xerosismentioning
confidence: 99%
“…The risk of skin dryness during treatment increases with age, pre-eczema, and prior cytotoxic use. Evidence showed patients who received gefitinib experienced xerosis cutis, acneiform have mean Transepidermal Water Loss values higher than normal (46). The different degrees of severity of the xerosis are illustrated in Figure 2.…”
Section: Xerosismentioning
confidence: 99%
“…The repeated tape stripping every 12 hours prevented full recovery of the skin barrier, which usually takes 24 hours [27,32], creating a chronically impaired skin barrier. Further, Chandra F, et al showed that EGFRI therapy causes increased transepidermal water loss (TEWL) of 11.5g/ m 2 h [33]. Although we did not measure TEWL in this study, ten tape strips have been shown to result in similar TEWL levels (e.g., 9.1g/m 2 h) [34].…”
Section: Discussionmentioning
confidence: 65%
“…30 Previous study showed that patients who are taking gefitinib experienced cutaneous side effects including xerosis cutis, acneiform eruptions, and paronychia, and had mean transepidermal water loss values higher than normal. 31 In our study, we evaluated the skin water content by the skin testing instrument to illustrate the efficacy of Zizao Yangrong granules.…”
Section: Discussionmentioning
confidence: 99%